Pemberdayaan, Pemulung, Sampah PEMBERDAYAAN PEMULUNG SAMPAH DITEMPAT PEMBUANGAN AKHIR (TPA) TAMANGNGAPA KECAMATAN MANGGALA PERSPEKTIF SYIASAH SYARIAH - Irfandi, Rifki; Risal, Chaerul; Jamil, M (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This study examines the empowerment of waste pickers at the Tamangngapa Final Waste Disposal Site (TPA) in Manggala District from the perspective of Siyasah Syar’iyah. The focus includes the realities of waste pickers’ lives, existing empowerment efforts, and an analysis based on Siyasah Syar’iyah principles. This qualitative research employs a syar’i and juridical approach. The findings reveal that waste pickers at TPA Tamangngapa live in highly concerning conditions, marked by limited education, inadequate skills, and poor living facilities. No specific empowerment programs from relevant institutions were found to target this group directly. From a Siyasah Syar’iyah perspective, this situation reflects a weak role of the state in protecting and empowering marginalized communities. The study recommends the development of government policies focused on empowering waste pickers based on social justice and Islamic legal principles to achieve sustainable well-being.